Sculture da Camera. - Swabian Castle, Bari (Bari : Assessorship for Culture of the Regione Puglia, 1986)
Andre, Carl ; Anselmo, Giovanni ; Armleder, John ; Alighiero e Boetti ; Borofsky, Jonathan ; Cadere, Andre ; Caldarelli, Biagio ; Ceccobelli, Bruno ; Cox, Stephen ; Cragg, Tony ; De Dominicis, Gino ; De Gennaro, Tullio ; Dellerba, Franco ; De Maria, Nicola ; Dokoupil, Jiri Georg ; Fisher, Joël ; Fischli & Weiss ; Fontana, Lucio ; Francisco, Richard ; etc.
Sculture da Camera / Chamer Sculptures, exhibition organized by the Bonomo gallery. The exhibition was presented in the halls of the Gypsoteca in the Swabian Castle at Bari in June 1986
boek